Multiple Relationship: Mengelola Batasan Hubungan Antara Konselor dan Konseli dalam Keberhasilan Konseling - Nasrudin, Alifia Hasna Putri; Budiman, Nandang; Nadhirah, Nadia Aulia (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2023)
Multiple relationships in counseling refers to a situation where a counselor or therapist has a professional relationship with more than one individual involved in the counseling process. The importance of managing multiple relationship boundaries for counselors is to avoid conflicts of interest, remain objective, and prevent potential exploitation or loss for clients. In this article, a systematic literature review method was used. Data was collected by processing literature from journals, books, articles and other sources.